Growth Response of Ipomoea Reptans Poir. Against The Application of Liquid Fertilizer Leachate Organic Waste With Superior Nutrients - Inggita Utami; Rahmah Sakinah; Ambar Pratiwi (Florea: Jurnal Biologi dan Pembelajarannya)
Leachate generally still has nutrients that can potentially optimize plant growth. However, according to the Ministry of Agriculture standards, the organic matter source can still not increase the test nutrient content of leachate liquid fertilizer. This study aimed to analyze the growth of Ipomoea reptans after applying leachate liquid fertilizer from superior nutrient materials and to determine the optimal concentration of leachate liquid fertilizer for the growth of Ipomoea reptans. This study was conducted using a Completely Randomized Design with the independent variables being variations in the concentration of leachate liquid fertilizer (P0 0%, P1 10%, P2 20%, and P3 30 %), and the dependent variable was the growth of Ipomoea reptans. The results showed that, at 36 DAP, P3 had the highest mean value for plant height, stem diameter, and the number of shoots. Treatment P0 had the highest average value for the parameter number of leaves. In contrast, treatment P2 had the highest mean for parameters of leaf area, root length, dry weight, and fresh weight. The application of liquid leachate fertilizer gave significantly different results only on the parameters of the length of the primary root and the fresh weight of the plant. The most optimal growth response of Ipomoea reptans was shown in the application of liquid leachate fertilizer with a concentration of 20%. This study's conclusions indicate that applying liquid fertilizer leachate from superior nutrient materials can increase the growth of Ipomoea reptans, especially at a concentration of 20%.